2010
DOI: 10.1159/000319626
|View full text |Cite
|
Sign up to set email alerts
|

<i>D</i>-Dimer Levels in Combination with Clinical Risk Factors Can Effectively Predict Subsequent Thromboembolic Events in Patients with Atrial Fibrillation during Oral Anticoagulant Therapy

Abstract: Objectives: Atrial fibrillation (AF) is associated with hemostatic abnormality and increased risk of thromboembolic events. The aim of the present study was to evaluate whether elevated D-dimer levels in combination with clinical risk factors can adequately predict subsequent thromboembolic events in patients with AF. Method: This was a post hoc analysis of the single-center, prospective observational study. Consecutive patients with nonvalvular AF (245 patients, 74 ± 9 years) treated with warfarin were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…Furthermore, numerous studies have shown that the D-dimer level can be a useful marker of the absence of left atrial appendage thrombi and subsequent embolic events in patients with NVAF, even during oral anticoagulation [15,16,17,18,19]. Meanwhile, in combination with CHADS 2 scores, the D-dimer level can effectively predict subsequent thromboembolic events in patients with NVAF [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, numerous studies have shown that the D-dimer level can be a useful marker of the absence of left atrial appendage thrombi and subsequent embolic events in patients with NVAF, even during oral anticoagulation [15,16,17,18,19]. Meanwhile, in combination with CHADS 2 scores, the D-dimer level can effectively predict subsequent thromboembolic events in patients with NVAF [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The D-dimer level, a coagulative marker of thrombogenesis, was found to be increased in patients with nonvalvular AF (NVAF) [12,13] and notably increased along with the accumulation of clinical risk factors [14]. In addition, multiple studies have shown that D-dimer levels can effectively predict subsequent embolic events in patients with NVAF, even during oral anticoagulant therapy [15,16,17,18,19]. Matsumoto et al [20] demonstrated that the plasma D-dimer level was significantly associated with infarction volume and poor functional outcome in NVAF patients with cardioembolic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of this investigation concluded that patients with acute atrial fibrillation have increased thrombogenesis (fibrin D-dimer) which persists for at least 30 days after successful cardioversion [12]. Furthermore, D-dimer levels in combination with clinical risk factors can effectively predict subsequent thromboembolic events in patients with atrial fibrillation during oral anticoagulant therapy [50]. This suggests that D-dimer as a biomarker has potential value in predicting cardiovascular events that are related to endothelial damage as well as in predicting thromboembolic events in atrial fibrillation secondary to abnormal thrombogenesis.…”
Section: Abnormal Thrombogenesis and Endothelial Dysfunctionmentioning
confidence: 99%
“…However, in our study the percentage of low risk patients (accordingly to the CHA 2 DS 2 -VASc score) with highest NT-proBNP was much higher than in the study performed by Hijazi and colleagues (14.3% versus 4.8%, respectively). It might be partly explained by the relatively small cohort in our pilot study, while another study analyzed patients from large anticoagulation trials.Several studies have demonstrated the usefulness of adding blood biomarkers to established clinical risk scores [6,7] but the application of this approach to the daily clinical practice still remains uncertain and the latest AF management guidelines [8] stress the focus on the identification of 'low' and 'truly low risk' patients who do not need any antithrombotic therapy. Therefore, the use of NT-proBNP might be clinically relevant to stratify the patients within the low risk CHA 2 DS 2 -VASc score 0 and 1.…”
mentioning
confidence: 99%
“…Several studies have demonstrated the usefulness of adding blood biomarkers to established clinical risk scores [6,7] but the application of this approach to the daily clinical practice still remains uncertain and the latest AF management guidelines [8] stress the focus on the identification of 'low' and 'truly low risk' patients who do not need any antithrombotic therapy. Therefore, the use of NT-proBNP might be clinically relevant to stratify the patients within the low risk CHA 2 DS 2 -VASc score 0 and 1.…”
mentioning
confidence: 99%